Analyzing Public Complaints on BPJS Health Services Through Platform X Using a Maqashid Shari'ah Perspective - Syarifah Salimah Nailulmuna; Abdul Mujib; Robiah Nuzul Hidayah; Fahmi Mustika Ramadhani; Bahrul Ulum (Hakamain: Journal of Sharia and Law Studies, 2025)
This study aims to explore public complaints directed at Indonesia’s Social Security Administration Agency (BPJS) as expressed on Platform X, through the analytical framework of Maqashid Shari’ah. Employing a qualitative research design, this study utilizes digital content analysis to examine and interpret public complaints posted on Platform X. The data were collected through purposive sampling of user-generated posts that explicitly criticized or questioned BPJS services, particularly in the context of health accessibility, affordability, and responsiveness. These complaints were then categorized thematically according to the five Maqashid Shari’ah indicators. The findings reveal significant dissatisfaction related to the preservation of life and wealth, as users reported delays in service provision, unclear administrative procedures, and unequal treatment across demographic and regional lines. Complaints also revealed emotional and psychological stress linked to navigating the system, suggesting broader implications for the protection of intellect and dignity. The study concludes that while BPJS has made notable progress in expanding healthcare access in Indonesia, critical shortcomings in implementation and service quality persist, undermining its alignment with the ethical objectives of Islamic law. This research contributes to academic discourse by bridging Islamic jurisprudential theory with digital ethnographic methods, offering a novel framework for evaluating public service institutions in Muslim-majority contexts. It also highlights the value of social media as a tool for gauging public sentiment and institutional accountability.